KARAKTERISASI FISIKOKIMIA BAKTERIOSIN YANG DIEKSTRAK DARI YOGHURT - Suarsana, I Nyoman (Buletin Veteriner Udayana, 2012)
In recent years, groups of antimicrobial peptides, mainly produced from lactic acidbacteria in yoghurt has been used extensively in the health field as an antibacterial andfood biopreservative. This aims of this study to determine the physicochemicalcharacterization and antimicrobial properties of bacteriocin which extracted from theyoghurt. We used Saphylococcus aureus and Eschericia coli bacteria for this trial. Weexamined physicochemical characters of the bacteriocin such as pH, thermal stability, andproteolytic effect. Also, we conducted the antimicrobial activties to S. aureus and E. coli.The results showed that the bacteriocin which extracted from the yoghurt could inhibit thegrowth of bacteria S.aureus, and E. coli. In order to, bacteriocin havephysicochemical properties, such as optimum active at pH 5, is stable against heating upto 121°C for 15 minutes, and sensitive to proteolytic enzymes
Keywords: bacteriocin, characterization of physicochemical, proteolytic enzyme, yoghurt.